Systolic Hypertension, Preeclampsia-Related Mortality, and Stroke in California. Issue 6 (June 2019) - Judy, Amy E.; McCain, Christy L.; Lawton, Elizabeth S.; Morton, Christine H.; Main, Elliott K.; Druzin, Maurice L.
Abstract : OBJECTIVE: To describe the clinical characteristics of stroke and opportunities to improve care in a cohort of preeclampsia-related maternal mortalities in California. METHODS: The California Pregnancy-Associated Mortality Review retrospectively examined a cohort of preeclampsia pregnancy-related deaths in California from 2002 to 2007. Stroke cases were identified among preeclampsia deaths, and case summaries were reviewed with attention to clinical variables, particularly hypertension. Health care provider– and patient-related contributing factors were also examined. RESULTS: Among 54 preeclampsia pregnancy-related deaths that occurred in California from 2002 to 2007, 33 were attributed to stroke. Systolic blood pressure exceeded 160 mm Hg in 96% of cases, and diastolic blood pressure was 110 or higher in 65% of cases. Hemolysis, elevated liver enzymes, and low platelet count syndrome was present in 38% (9/24) of cases with available laboratory data; eclampsia occurred in 36% of cases. Headache was the most frequent symptom (87%) preceding stroke. Elevated liver transaminases were the most common laboratory abnormality (71%). Only 48% of women received antihypertensive treatment. A good-to-strong chance to alter outcome was identified in stroke cases 66% (21/32), with delayed response to clinical warning signs in 91% (30/33) of cases and ineffective treatment in 76% (25/33) cases being the most common areas for improvement. CONCLUSION: Stroke is the major cause of maternal mortality associated with preeclampsia or eclampsia. All but one patient in this series of strokes demonstrated severe elevation of systolic blood pressure, whereas other variables were less consistently observed. Antihypertensive treatment was not implemented in the majority of cases. Opportunities for care improvement exist and may significantly affect maternal mortality. Abstract : Severe systolic hypertension and patient- and health care provider–related factors are associated with preeclampsia-related mortalities from stroke in California.